1995
DOI: 10.1002/cne.903620412
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the face and intraoral structures in area 3b of the squirrel monkey (Saimiri sciureus) somatosensory cortex, with special reference to the ipsilateral representation

Abstract: Studies of the representation of the trigeminal nerve in the thalamus and cerebral cortex of mammals have revealed representations of both contra- and ipsilateral intraoral structures. However, the relative extent of both representations is subject to considerable species variation. The present study employed microelectrode mapping and anatomical tracing to investigate the location and extent of the ipsilateral representation in area 3b of the somatosensory cortex of squirrel monkeys. A small region, approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 31 publications
2
44
1
Order By: Relevance
“…Determination of the somatotopy of the face and the oral representation in cortical area 3b of New World owl monkeys and squirrel monkeys using electrophysiological mapping by microelectrodes and histological procedures found that the palate SI area was microscopically adjacent to, or within, the tongue SI area of a few square millimeters (Jain et al 2001). Closer location of the tongue and palate SI cortices has been demonstrated in monkeys by other microelectrode studies (Cusick et al 1986;Manger et al 1995). Since the stimulation points of the palate included the gingiva, these results in monkeys support our present observation that the gingiva area is adjacent to the tongue area in humans.…”
Section: Discussionmentioning
confidence: 88%
“…Determination of the somatotopy of the face and the oral representation in cortical area 3b of New World owl monkeys and squirrel monkeys using electrophysiological mapping by microelectrodes and histological procedures found that the palate SI area was microscopically adjacent to, or within, the tongue SI area of a few square millimeters (Jain et al 2001). Closer location of the tongue and palate SI cortices has been demonstrated in monkeys by other microelectrode studies (Cusick et al 1986;Manger et al 1995). Since the stimulation points of the palate included the gingiva, these results in monkeys support our present observation that the gingiva area is adjacent to the tongue area in humans.…”
Section: Discussionmentioning
confidence: 88%
“…In Figure 2 of [24] the distance between upper lip to lateral face in the squirrel monkey is 2 mm. In Figure 3 and 4 of [25] the distance from upper lip and side of face is about 2 mm. The distance from lateral orbit to upper lip in the squirrel monkey is about 2 cm.…”
Section: Discussionmentioning
confidence: 96%
“…Much of the oval is devoted to the contralateral tongue, but a more rostral part is devoted to the ipsilateral tongue. O3 responds to ipsilateral teeth, while O4 responds to ipsilateral tongue (for a somewhat different interpretation of the representation of the face and oral structures in squirrel monkeys, see Manger et al, 1995). A similar arrangement appears to exist in prosimian galagos (Fig.…”
Section: Representation Of Tongue and Teeth In Area 3b And Adjoining mentioning
confidence: 92%